2021
DOI: 10.1007/s11033-021-06389-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of suitable reference genes for expression studies in pomegranate under different biotic and abiotic stress conditions

Abstract: Pomegranate (Punica granatum) is an important economic fruit crop, facing many biotic and abiotic challenges during cultivation. Several research programs are in progress to understand both biotic and abiotic stress factors and mitigate these challenges using gene expression studies based on the qPCR approach. However, research publications are not available yet to select the standard reference gene for normalizing target gene expression values in pomegranate. The most suitable candidate reference gene is requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…It was also found that GAPDH maintained stable expression in different organs and at different stages of fruit development in strawberry [25]. Both GAPDH and CYP maintained good stability in pomegranate when subjected to biotic and abiotic stresses [26]. The most consistently expressed reference genes in blueberry were UBC9 and GAPDH when attacked by Monilinia vaccinii-corymbosi [27].…”
Section: Discussionmentioning
confidence: 86%
“…It was also found that GAPDH maintained stable expression in different organs and at different stages of fruit development in strawberry [25]. Both GAPDH and CYP maintained good stability in pomegranate when subjected to biotic and abiotic stresses [26]. The most consistently expressed reference genes in blueberry were UBC9 and GAPDH when attacked by Monilinia vaccinii-corymbosi [27].…”
Section: Discussionmentioning
confidence: 86%
“…As a result, hundreds of transcriptome profiling studies have been carried out to date, proving that RNA-seq is an advanced method to decipher the molecular mechanism underlying these interactions [ 11 ]. Simultaneously, these approaches would aid in the continuous identification of new resistance genes, which is crucial in setting the stage for upcoming breeding programs and improving resistance to biotic stresses [ 12 , 13 ]. For instance, 186 R2R3-MYB transcription factors (TFs), identified from pomegranate genome, are involved in regulating plant development, metabolite accumulation, and defense responses; similar occurs for U-box gene family entailed in abiotic stresses [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the cultivation of pomegranate provides a source of livelihood to over 2.5 lakh families in India (NRCP Annual Report, 2020). Although persistent efforts are being made in India to improve, promote and market the crop, various factors such as abiotic and biotic stressors, physiological limitations, genetic constraints, excessive growth rate, nutrient unavailability, as well as pest and disease infestations, have been identified as severe impediments to its growth 4 , 5 . Diseases such as wilt complex 6 , anthracnose 7 , bacterial blight 8 , Coniella fruit rot 9 , 10 , foliar diseases such as leaf spot and fruit spot disease 11 are some of the major diseases that affect the pomegranate crop.…”
Section: Introductionmentioning
confidence: 99%